Transformação do trabalho administrativo em trabalho operacional: um estudo exploratório na área de TI de uma instituição financeira - Franco Júnior, José Roberto de Melo (2009)
Two large sectors of the economy that are in the transitional stage of personal decisions (for administrators) for institutional decisions (based on systems). The survey was conducted as a series of structured interviews applied to all (forty) of the administrators of a given hierarchical level of an IT department of a large financial institution of São Paulo called leadership in this financial institution. The study took place during an organizational transition. A portion was already working under the personal approach and the other based on a system approach. The results were proof that administrative work has become operational and the identification of features and scope of influence of this transformation. Using the criterion of separation between administrative and operational work of Simon, it becomes possible to compare two people and say who spends more or less time with administrative activities. This criterion based on the time spent is what was used to conduct the research. It was concluded that a simple questionnaire would not be able to give valid results in terms of cognitive psychology and a lot of care would be taken even if it used an interview to have evidence of reliability and validity suggested by Stabein to a relevant work. The results were processed and analyzed from the qualitative point of view to serve the purpose of identifying the transformation of administrative work in operational work. The characteristics found were that this transformation has a behavior of imposition; the quality of the result depends on the maturity of existing processes and affects self-image of the administrator. Synthesizing the scope found in a single sentence, it becomes: "People management, process management and software management